A mathematical formulation of the valuation of ether and ether derivatives as a function of investor sentiment and price jumps - Rebecca Abraham; Hani El-Chaarani (Journal of Risk and Financial Management, 2022)
The purpose of this study was to create quantitative models to value ether, ether futures, and ether options based upon the ability of cryptocurrencies to transform existing intermediary-verified payments to non-intermediary-based currency transfers, the ability of ether as a late mover to displace bitcoin as the first mover, and the valuation of ether in the context of investor irrationality models. The risk-averse investor's utility function is a combination of expectations of the performance of ether, expectations of cryptocurrencies' transformative power, and expectations of ether superseding bitcoin. The moderate risk-taker's utility function is an alt-Weibull distribution, along with a gamma distribution. Risk-takers have a utility function in the form of a Bessel function. Ether price functions consist of a Levy jump process. Ether futures are valued as the combination of current spot prices along with term prices. The value of spot prices is the product of a spot premium and a lognormal distribution of spot prices. The value of term prices is equal to the product of a term premium, and the Levy jump process of price fluctuations during the delivery period. For ether options, a less risky ether option portfolio offsets ether's risk by a fixed-income trading strategy.
Keywords: 650; alt-Weibull distribution; ether futures; ether options; ether valuation; generalized exponential distribution; Levy jump process